(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
In a significant public health development, the Karnataka government has proposed making sudden out-of-hospital deaths, particularly in individuals under 45, a notifiable condition. This initiative, driven by expert committee recom mendations, also mandates autopsies in such cases and the creation of a centralized registry. By aligning with interna tional best practices and emphasizing data-driven strategies, this model addresses India’s long-standing gaps in mortality surveillance. While ethical and logistical challenges persist, Karnataka’s policy can serve as a national blueprint for reforming death investigation and improving cardiovascular health outcomes.